Medical Interns’ Self-Evaluation of Clinical Skills Training in the Emergency Department at Babol University of Medical Sciences - Zahra Rostamtabar; Sobhan Rahimi Esbo; Mehdi Mohammadian Amiri; Hemmatollah Gholinia Ahangar; Maryam Ghaemi-Amiri (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Mastery of clinical skills in emergency medicine is a key factor in effectively managing emergency patients. Given the critical importance of acquiring these skills, this study aimed to evaluate the self-assessment of medical interns at Babol University of Medical Sciences regarding their training and competence in the emergency department Materials and methods: This study was conducted as a descriptive cross-sectional study on 100 interns from Babol University of Medical Sciences who had completed their emergency medicine internship in 2023. Participants completed demographic questionnaires and satisfaction surveys assessing their acquisition of clinical skills in managing emergency patients, performing essential therapeutic procedures, and their education in the emergency department. Data were analyzed using SPSS version 27 with descriptive and inferential statistical methods. Results: The mean age of the students was 25.54±1.42 years. The results showed that students reported the highest satisfaction in the areas of acquiring clinical skills for managing emergency patients, performing primary therapeutic procedures, and the quality of education in the emergency department, specifically in handling abdominal pain, nasogastric tube insertion, gastric lavage, and the impact of the emergency medicine department on improving emergency activities. Conversely, the lowest satisfaction was reported in dealing with environmental emergencies, airway management, and motivating learners for study and research activities. Conclusion: Based on the results of this study, there is a clear need for targeted planning and strategies to enhance clinical skills in managing environmental emergencies, improving airway management, and motivating interns to engage in study and research activities.